The implementation of building information modeling (BIM) towards sustainable construction industry in Egypt - Mohamed, Amira Elshazly (AUC Knowledge Fountain, 2019)

(untitled)
Global environmental changes, energy consumption, and the scarcity of water have all imposed the need to implement sustainable development strategies worldwide. The construction industry and its healthy practices are not exception, as it should take more strides to alleviate harmful impacts of unsustainable construction practices on the built environment. Sustainable construction has many aspects such as passive design, selection of the appropriate materials and construction techniques, energy efficient systems, and water conservation. In Egypt, current situation regarding energy consumption, accelerated urbanization, and high pollution rates are urging the Architecture, Engineering, and Construction (AEC) professionals to convert current conventional construction approaches into more sustainable ones. One of the useful in this regard is to capitalize on technological innovative means to narrow the gap and advance the sustainable green construction mission. Building Information Modeling (BIM) is a relatively recent technology within the construction industry that, when properly introduced, can help in providing adequate project quality, accurate time and quantity take-offs schedules, and project costs reduction. For instance, this tool can result in more efficient design practices, which contribute to reducing waste generation, energy consumption and promote passive design strategies. This study aims at analyzing the impact of BIM implementation on the sustainable construction practices and assessing current BIM implementation trends during the design process phase in the AEC industry. In principle, the study tackles BIM adoption situation factors of influencing and the barriers, and opportunities confronting its implementation within the Egyptian consultancy firms. Building on the literature review, this study discusses the sustainable design and constructability concepts in the construction industry and the manner by which BIM can be effectively utilized the pre-construction phase. Furthermore, the study describes the BIM implementation obstacles, success factors, and the role of government and other stakeholders in adopting BIM for achieving sustainable construction industry. To meet this objective, interviews were conducted with BIM users and experts to investigate the BIM implementation situation in the Egyptian consultancy firms and needed actions for successful BIM adoption in the Egyptian construction market. The academic knowledge with the interviews provide the researcher with the base to articulate the ideas and develops the discussion to figure out the critical issues regarding BIM adoption in Egypt. In this manner, the research provides some recommendations for successful BIM adoption in the Egyptian construction industry. In addition, the study recommended adopting BIM as the technological pillar towards sustainable construction industry in the country's 2030 sustainable development strategy. The research also encourages the collaboration between the construction industry stakeholders to set a roadmap for adopting BIM in the Egyptian construction industry. Finally, build on the literature and the experts' opinions, the research recommended practical actions for the industry players to ensure a successful transition towards BIM implementation.